Respuesta :

Answer:

Step-by-step explanation:

[tex]\displaystyle\\F(6)\ \ \ \ \frac{15}{x-3} \\\\\frac{15}{6-3}= \\\\\frac{15}{3}= \\\\5\\\\F(a)\ \ \ \ \ \frac{15}{x-3} \\\\F(a)=\frac{15}{a-3}[/tex]

Answer:

5 and [tex]\frac{15}{a-3}[/tex]

Step-by-step explanation:

given

f(x) = [tex]\frac{15}{x-3}[/tex]

f(6) means what is the value of f(x) when x = 6

substitute x = 6 into f(x)

f(6) = [tex]\frac{15}{6-3}[/tex] = [tex]\frac{15}{3}[/tex] = 5

f(a) means what is the value of f(x) when x = a

substitute x = a into f(x)

f(a) = [tex]\frac{15}{a-3}[/tex]